Synthesis, Biological Activities and DFT Calculation of a-Aminophosphonate Containing Cyclopropane Moiety - Liu, Xing-Hai; Weng, Jian-Quan; Tan, Cheng-Xia; Pan, Li; Wang, Bao-Lei; Li, Zheng-Ming (Asian Journal of Chemistry, 2011)
Five new a-aminophosphonate derivatives containing cyclopropane moiety have been synthesized via conventional and microwave irradiation methods under solvent- and catalysis-free condition. The structures of the a-aminophosphonate compounds have been confirmed by 1H NMR, 31P NMR, FT-IR, EI-MS and FTICR-MS studies. Their herbicidal activities were evaluated in vivo and in vitro. The results showed some compounds were found to exhibit moderate herbicidal activities against Brassica campestris at 100 and 10 ppm. Theoretical calculation of 2c was carried out with B3LYP/6-31G (d,p). The full geometry optimization was carried out using 6-31G(d,p) basis set and the structure-activity relationship was also studied by frontier orbital energy.